Faktor-Faktor Yang Mempengaruhi Keputusan Investasi Pada Generasi Z - Zain Taufiq; Setiyo Purwanto; Fathihani (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2023)
This study investigates the influence of financial literacy, locus of control, psychological factors, and demographic factors on the investment decisions of Generation Z. The results show that good financial literacy, a positive locus of control, as well as psychological factors such as self-confidence and risk-taking ability, have a significant impact on the investment decisions of Generation Z. Additionally, demographic factors such as occupation, age, and education also play a crucial role in their investment decision-making. Despite the significant effects of these variables, the study also finds the existence of other factors influencing the investment decisions of Generation Z. Generation Z is advised to invest wisely by choosing financial institutions regulated by the OJK (Financial Services Authority of Indonesia), avoiding potential scams, and considering investment diversification to mitigate risks